Samuel as Jack-in-the-Box: The Woman of Endor as a Hidden Polemical Story - Roi, Micha (Scandinavian journal of the Old Testament, 2024)
This article takes a fresh approach to the story of the woman of Endor (1 Sam 28,3-25), arguing that the difficulties it raises serve as the key for understanding the story’s polemical intent. The affinities between Samuel and the medium and their professional success indicate that Israelite prophecy and pagan manticism are one and the same. The antithesis between them and between the woman’s empathy for Saul and Samuel’s antagonism towards Saul both evince Samuel’s inferiority to the medium. Even if only adduced in order to cast a shadow over Samuel, the necromancer’s positive depiction creates the impression that belongs to a later period during which belief in necromancy was less threatening. This impression is reinforced by linguistic and substantive considerations. The reference to the war against Amalek, and Samuel’s religious declaration that heeding God’s word is more pleasing to him than cultic ritual, disclose the author’s priestly identity.